2021
DOI: 10.1371/journal.pone.0258319
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic microangiopathy after kidney transplantation: Analysis of the Brazilian Atypical Hemolytic Uremic Syndrome cohort

Abstract: Background Atypical Hemolytic Uremic Syndrome (aHUS) is an ultra-rare disease that potentially leads to kidney graft failure due to ongoing Thrombotic Microangiopathy (TMA). The aim was evaluating the frequency of TMA after kidney transplantation in patients with aHUS in a Brazilian cohort stratified by the use of the specific complement-inhibitor eculizumab. Methods This was a multicenter retrospective cohort study including kidney transplant patients diagnosed with aHUS. We collected data from 118 transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…However, some studies showed that early use of eculizumab did not help the kidneys of patients with AHUS [ 33 ], and their studies have certain limitations. When to discontinue the drug after use is also important in the eculizumab approach to evaluate AHUS recurrence [ 16 , 34 ]. Two studies mentioned that eculizumab was once recommended for lifelong treatment, but a prospective phase 4, multicenter, uncontrolled study provided evidence that once complete remission is achieved, most patients with AHUS are safe to discontinue eculizumab [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies showed that early use of eculizumab did not help the kidneys of patients with AHUS [ 33 ], and their studies have certain limitations. When to discontinue the drug after use is also important in the eculizumab approach to evaluate AHUS recurrence [ 16 , 34 ]. Two studies mentioned that eculizumab was once recommended for lifelong treatment, but a prospective phase 4, multicenter, uncontrolled study provided evidence that once complete remission is achieved, most patients with AHUS are safe to discontinue eculizumab [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…renal function improvement upon treatment critically depends on the time interval between aHUS onset and eculizumab start: the shorter, the better. 86,90 Similarly, the use of eculizumab in kidney transplant recipients with aHUS resulted in a highly significant decrease in TMArelated graft loss rates, as evidenced by nationwide studies carried out in Brazil, 91 France, 33 and USA. 92 As a striking consequence, the proportion of aHUS under chronic dialysis was halved over 5 years in France, following eculizumab approval.…”
Section: C5 Blockade In Ahusmentioning
confidence: 98%
“…aHUS is a rare genetic disease and the knowledge of its epidemiological data, natural history, genetic profile and pathophysiology have been increasing over recent years [ 5 ]. However, reports from low-middle income countries' populations of aHUS are restricted to a few cohort series [ 6–12 ]. The availability of data from these countries can broaden the spectrum of genotype according to the region.…”
Section: Introductionmentioning
confidence: 99%